Electrochemical supercapacitors of electrodeposited PANI/H-RuO2 hybrid nanostructure - Shaikh, ShoyebMohamad F.; Lim, Ji Yeon; Joo, Oh-Shim (ELSEVIER SCIENCE BV, 2013)
Electrodeposited mixed nanostructures composed of conducting polyaniline (PANI) and hydrous ruthenium oxide (H-RuO2) referred as a hybrid nanostructure was synthesized. The surface morphology was investigated from the field-emission scanning electron microscopy digital photoimages. Fibrous network of PANI and spheres of H-RuO2 were obtained. PANI embedded H-RuO2 was confirmed from the Raman spectroscopy analysis. Cyclic-voltammetry, used to characterize the electrochemical capacitive properties of hybrid PANI/H-RuO2 (RP 30) nanostructure, showed a specific capacitance as high as 322 F/g in 0.5 M H2SO4 electrolyte. The electrochemical impedance spectroscopy measurement revealed the low equivalent series resistance. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: RAMAN-SPECTROSCOPY; CAPACITORS; PERFORMANCE; POLYANILINE